Foundation phase teachers’ views of the involvement of male caregivers in young children’s education - Mzoli Mncanca; Sarita Ramsaroop; Nadine Petersen (South African Journal of Childhood Education, 2021)
Background: Studies in South Africa show a high prevalence of male caregiver absence in the lives of children under the age of 9 years. In this respect, foundation phase teachers are well positioned to provide input and shed light on how schools can contribute towards improving male caregiver involvement in their children’s early education.